Evaluación del efecto antimicrobiano de la adición de aceite esencial de albahaca morada Ocimum sanctum en embutido de cerdo. - Zambrano Santillán, Ángel Ricardo (2024)
The purpose of this research is to evaluate the addition of purple basil Ocimum sanctum essential oil as an antimicrobial agent in pork sausage. The variables evaluated were microbiological parameters of the pork sausage with levels of 10,15 and 20 percent of purple basil essential oil and sensory analysis of the pork sausage. The research was carried out in the laboratories of the Faculty of Agricultural Sciences. The extraction of purple basil essential oil will be carried out using the steam arrest extraction method using clevenger equipment. Six treatments were carried out with two repetitions, with different percentages of black basil essential oil with equivalence of 10%, 15% and 20% of which T1, T3 and T5 were carried out by the blanching conservation method and treatments T2 , T4 and T6 by the smoking method. For the determination of Escherichia coli and Coliform bacteria, micro fast seeding plates were used. The results indicated that there is no presence of Escherichia coli and Coliform. In the sensory analyzes regarding color, aroma, flavor and texture, acceptance was obtained from the panelists.